Considerations on the concept of revolution and its relations with the ideas of time and history: in search of a contemporary notion - Raphael Guazzelli (2023)
The article explores the development of the concept of revolution in modernity. We start from the hypothesis, formulated by Lazzarato, who claims that the abandonment of the idea of revolution is the reason for the political and theoretical defeat of critical thinking after May 68. Next, we trace a brief genealogy of the concept of revolution, focusing on the legacy of the French Revolution. In this part we use the analyzes of the classic study by Koselleck, but also from the Foucauldian reading of Kant. A third moment is dedicated to the critique between the conception of time and its relationship with history in the work of Giorgio Agamben. The Italian, supported by Walter Benjamin, argues that Marxism lacked a radical understanding of time as relevant as its conception of history. Finally, we explore the dichotomy of uprising and revolution in an attempt to open other argumentative hypotheses to critical thinking from the idea of suspension of historical time present in a study by another Italian, Furio Jesi.